Effects of torrefaction on product distribution and quality of bio-oil from food waste pyrolysis in N2 and CO2. (15th March 2022) - Ly, Hoang Vu; Kwon, Byeongwan; Kim, Jinsoo; Oh, Changho; Hwang, Hyun Tae; Lee, Jung Suk; Kim, Seung-Soo
Graphical abstract: Highlights: Feedstock of mixed food waste pretreated by torrefaction showed high HHVs. Pyrolysis bio-oils contained high aliphatic hydrocarbon and phenol contents. Using CO2 in pyrolysis promoted the formation of alkanes, alkene in bio-oils. Pyrolysis in CO2 medium inhibited the formation of harmful compounds to environment. More CO generated in CO2 -pyrolysis of torrefied mixed food waste. Abstract: Waste food utilization to produce bio-oil through pyrolysis has received increasing attention. The feedstock can be utilized more efficiently as its properties are upgraded. In this work, the mixed food waste (MFW) was pretreated via torrefaction at moderate temperatures (250–275 °C) under an inert atmosphere before fast pyrolysis. The pyrolysis of torrified MFW (T-MFW) was performed in a bubbling fluidized-bed reactor (FBR) to study the influence of torrefaction on the pyrolysis product distribution and bio-oil compositions. The highest liquid yield of 39.54 wt% was observed at a pyrolysis temperature of 450℃. The torrefaction has a significant effect on the pyrolysis process of MFW. After torrefaction, the higher heating values (HHVs) of the pyrolysis bio-oils (POs) ranged from 31.51 to 34.34 MJ/kg, which were higher than those of bio-oils from raw MFW (27.69–31.58 MJ/kg). The POs mainly contained aliphatic hydrocarbons (alkenes and ketones), phenolic, and N-containing derivatives. The pyrolysis of T-MFW was also carried out under the CO2 atmosphere. The application of CO2 as a carrier gas resulted in a decrease in the liquid yield and an increase in the gas product yield. In addition, the carbon and nitrogen content of POs increased, whereas the oxygen was reduced via the release of moisture and CO. Using CO2 in pyrolysis inhibited the generation of nitriles derivatives in POs, which are harmful to the environment. These results indicated that the application of CO2 to the thermal treatment of T-MFW could be feasible in energy production as well as environmental pollution control.